The development of ocean currents and the response of the cryosphere on the Southwest Svalbard shelf over the Holocene - Dhanushka Devendra; Magdalena Łącka; Natalia Szymańska; Małgorzata Szymczak- Zyła; Magdalena Krajewska; Agnes K M Weiner; Stijn De Schepper; Margit H Simon; Marek Zajączkowski (PANGAEA, 2025)
We present multi-proxy data, including benthic foraminiferal assemblages, carbon and oxygen stable isotopes, total organic carbon (TOC) and total carbon (TC), ice-rafted debris (IRD), x-ray fluorescence, biomarkers (alkenones, sterols), and pigment data, covering the past 11.4 kyr BP. These data are derived from sediment core OCE2019-HR7-GC, retrieved from the Southwest Svalbard shelf (76°56.513 extquotesingleN, 14°54.072 extquotesingleE, 133 m water depth) during the AREX 2019 expedition aboard RV Oceania. Benthic stable isotopes were primarily measured on Elphidium clavatum. The dataset is presented in relation to both age and depth.